Lewis Acid Induced Functionalization of Photoluminescent 2D Silicon Nanosheets for the Fabrication of Functional Hybrid Films. (29th March 2017) - Helbich, Tobias; Lyuleeva, Alina; Marx, Philipp; Scherf, Lavinia M.; Purkait, Tapas K.; Fässler, Thomas F.; Lugli, Paolo; Veinot, Jonathan G. C.; Rieger, Bernhard
Abstract : Various Lewis acids are found to efficiently catalyze hydrosilylation reactions of hydride‐terminated 2D silicon nanosheets at room temperature. The hydride‐terminated nanosheets can be functionalized with a variety of unsaturated functional substrates and still possess their unique characteristic (opto)electronic properties (e.g., photoluminescence). This is demonstrated by successfully implementing the readily functionalized materials into new silicon/semiconducting polymer‐based field‐effect transistors (FETs). Surface modification of the freestanding silicon nanosheets opens new possibilities to form highly homogeneous blends with the already broadly used conventional polymers poly(3‐hexylthiophene‐2, 5‐diyl). The consequential combination of the different properties of the materials enables the enhancement of the sensitivity of the solution‐gated FETs and increases the transconductance of the operating device. Abstract : Different Lewis acids are used to catalyze hydrosilylation reactions on silicon nanosheets to modify the surface with different functional substrates. The resulting hybrid material exhibits outstanding (opto)electronic properties, which is shown by the fabrication of silicon nanosheet/semiconducting polymer‐based field‐effect transistors with enhanced sensitivity and increased transconductance.